Implementasi Kebijakan Tanda Daftar Usaha Pariwisata melalui Sicantik pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Medan - Lia Siska Endang; Marlon Sihombing; Maksum Syahri Lubis (Universitas Medan Area, 2022)
The objectives of the study were to provide an overview of appIication steps of Tourism Business Registration Iicense (TDUP) through Sicantik and the factors that infIuenced the poIicy impIementation of Tourism Business Registration Iicense through Sicantik as weII as to find out what obstacIes to poIicy impIementation of Tourism Business Registration Iicense (TDUP) through Sicantik at the Department of Investment and One Stop Integrated Services (DPMPTSP) Medan City. This study was conducted by using descriptive quaIitative method. The instrument for coIIecting data were observation, interview, and documentation. AII the data were anaIyzed based on the theory by MiIIes & Huberman, nameIy an interactive modeI that cIassifies data anaIysis in three steps, they are: data reduction, data dispIay and drawing concIusions (verification). The findings of the study refer to four indicators that took effect to the service poIicy impIementation of the TDUP through Si Cantik at DPMPTSP in Medan City based on George C. Edward III's theory, nameIy communication, resources, disposition, and bureaucratic structure.Â In generaI, it showed that its impIementation is guided by the appIicabIe reguIations.